2018
DOI: 10.1371/journal.pone.0199048
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the pathogenic role and genotype-phenotype correlation of the USH2A p.(Cys759Phe) variant among Spanish families

Abstract: IntroductionMutations in USH2A cause both isolated Retinitis Pigmentosa (RP) and Usher syndrome (that implies RP and hearing impairment). One of the most frequent variants identified in this gene and among these patients is the p.(Cys759Phe) change. However, the pathogenic role of this allele has been questioned since it was found in homozygosity in two healthy siblings of a Spanish family. To assess the causative role of USH2A p.(Cys759Phe) in autosomal recessive RP (ARRP) and Usher syndrome type II (USH2) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 65 publications
1
33
0
Order By: Relevance
“…In cytoplasmatic domains 2-4 (included in the transmembrane region in Figure 3), the observed frequency of nonsense variants was higher than expected (p-value: 0.002952). In the McMillan et al study conducted in 2004 [211], the generated mouse model that encoded only the ectodomains of the ADGRV1 gene manifested audiogenic seizures in a manner that clarified the implication of cytoplasmic and transmembrane domains in the auditory function [212].…”
Section: Adgrv1mentioning
confidence: 99%
See 1 more Smart Citation
“…In cytoplasmatic domains 2-4 (included in the transmembrane region in Figure 3), the observed frequency of nonsense variants was higher than expected (p-value: 0.002952). In the McMillan et al study conducted in 2004 [211], the generated mouse model that encoded only the ectodomains of the ADGRV1 gene manifested audiogenic seizures in a manner that clarified the implication of cytoplasmic and transmembrane domains in the auditory function [212].…”
Section: Adgrv1mentioning
confidence: 99%
“…Similarly, a cohort of 57 patients carrying p.Cys759Phe (p.C759F) was studied using HTS by Pérez-Carro et al with the purpose of clarifying the role of this variant as either a RP-causing variant or a possible phenotype modifier [212]. In this study, patients were classified into three categories: the first included patients homozygous for the p.C759F variant; the second contained compound heterozygous patients for p.C759F with another missense variant; and the third compiled compound heterozygous patients for p.C759F with a truncating mutation.…”
Section: Ush2amentioning
confidence: 99%
“…Another common pathogenic variant, also located in exon 13, is the missense mutation c.2276 G > T, p. Cys759Phe (rs80338902) accounting for 7.6% of the pathogenic variants according to the LOVD database (191/2484). The replacement of a cysteine by a phenylalanine has been predicted to disrupt a presumed disulphide bond or lead to the rearrangement of a key region promoting interactions with the extracellular matrix, impairing the function of usherin ( Pérez-Carro et al, 2018 ; Rivolta et al, 2002 ). A further relatively frequent mutation driving a diseased phenotype by a different mechanism is the deep-intronic c.7595-2144 A > G mutation (rs786200928) in intron 40 of USH2A .…”
Section: Genetics Of Ush2amentioning
confidence: 99%
“…96 They proposed an allelic hierarchy model in which the presence of at least one retinal diseasespecific allele in a patient with USH2Arelated retinopathy resulted in the preservation of hearing. While this has not been supported by subsequent studies, 6,98,99 the same analysis on a different cohort 100 combined with two large external cohorts 98,101 found that the allelic hierarchy model was valid in 86% of individuals with nonsyndromic USH2ARP. 100 In addition, it has been reported that Usher 2 patients with one copy of the p.(Cys759Phe) allele showed a later onset of RP and milder hear ing loss compared with the general Usher 2 popu lation, 6 and the presence of the p.(Cys759Phe) variant in a homozygous state or in combination with other USH2A missense mutations has been associated with isolated RP or RP with late onset hearing loss.…”
Section: Genotype-phenotype Correlationsmentioning
confidence: 84%
“… 100 In addition, it has been reported that Usher 2 patients with one copy of the p.(Cys759Phe) allele showed a later onset of RP and milder hearing loss compared with the general Usher 2 population, 6 and the presence of the p.(Cys759Phe) variant in a homozygous state or in combination with other USH2A missense mutations has been associated with isolated RP or RP with late onset hearing loss. 99 In contrast, the p.(Glu767Serfs*21) variant results in a more rapid deterioration and severe hearing threshold, heralding the need for careful audiological monitoring and consideration of cochlear implants. 100 In general, severe hearing impairment has been associated with truncating variants in USH2A.…”
Section: Genetics Of Usher Syndromementioning
confidence: 99%